A Bécsi Egyetem magyarországi diákjai a középkorban: Kiegészítő adatok: karok és fokozatszerzés - Kelényi, Borbála (Per Aspera ad Astra, 2017)
This paper discusses the students from the medieval Hungarian Kingdom at the University of Vienna. It is well-known that the majority of the Hungarian students attended the University of Vienna and the research of the topic has been favoured since the list of the students between 1365 and 1526 was published by Anna Tüskés. The researcher accomplished a grandiose work by collecting systematically the data of the 7,213 students from the sources. Anna Tüskés already intended to gather the data about the Hungarian students’ choice of faculty or faculties and about their graduation also. She managed to identify the faculty in the case of 843 students. However, some further databases have come to light since her publication, which allow the expansion of her data. The graduation-list of the faculty of arts e.g. was available previously till 1416, but it was published till 1555 after 2008. Consequently this paper aims at collecting the students’ choice of faculty or faculties or their graduation. The examination of the University of Vienna has an outstanding importance for that reason that all the four faculties (arts, law, medicine and theology) were allowed to teach by papal permission. Moreover, the data are especially significant, since almost only the data about the faculty of arts are remained in the case of the University of Kraków, which was the second most popular with the Hungarian students. The examination of the newer sources allowed to modify the number of the Hungarian students in Vienna (6,785 persons) and to identify the faculty’s choice of 2,107 attendee. It is beyond doubt, that the most undergraduate gained their degree at the faculty of arts (1,921 persons). The majority of them attended only this faculty. Much fewer Hungarians preferred the faculty of law (349 persons). Infinitesimal students from the Hungarian Kingdom were interested in studying at the faculties of medicine (18 persons) and theology (35 persons). The timelines of the matriculation or graduation at each faculty are similar to the main tendencies, concerning e.g. both to the timeline of the main and first registration of a Hungarian student at the University of Vienna and to the timeline of all Viennese students’ matriculation or graduation.